Philippine multilingual medical thesaurus on diseases pathological conditions, signs, and symptoms in Kapampangan - Lu, Jan Alexis L. (2016)
For the past 20 years, medicine has been improving because of the advances in information technologies and discoveries in the field of biological sciences. The continuous growth in medicine gives more language and communication barrier towards the patients and even the medical practitioners. This study was conducted in order to translate MeSH terms on Disease Pathological conditions, signs, and symptoms in Kapampangan language and to have this study included in the Philippine Multilingual Medical Thesaurus. The terms were acquired from the MeSH online browser from Category C23 - Disease: Pathological signs, conditions and symptoms. The terms were translated through dictionary ranking and consulted native speakers of Pampanga. The researcher consulted 5 medical practitioners and 6 non-medical practitioners who are native speakers of Kapampangan. The researcher provided a translation sheet with more than 800 medical terms. They provided translated terms that helped the researcher in comparing the tr erms and analyzing it using the triangulation technique. The researcher also arranged the terms alphabetically so the users can easily comprehend the thesaurus. This study was able to translate 180 terms; 21.13% have Kapampangan translated terms and 78.87% terms have no Kapampangan translated terms.